Acadêmicos da UFRGS e comissão especial de investigação sumária no ano de 1964 - Cerutti, Marcos Fontana (Universidade do Vale do Rio dos Sinos, 2010)
The Special Commission of Summary Investigation (SCSI) placed at UFRGS soon after the military coup/64, had the aim of investigating the subversive acts of the teachers, employees and students inside the institution. This research looks for knowing how that happening reverberated along the life trajectory of some students involved in that context. For that, it uses the oral history methodology, through five interviews, beyond document analysis (records, testimonies transcriptions, information lists, and letters) and Correio do Povo newspaper articles from 1964. The research refers to the society of that time, highlighting the political and social effervescence environment, the student movement in Rio Grande do Sul in the decade of 1960 and it concludes based on consideration concerning the research process, which deals with memory and with some findings about the institutionalized repression at UFRGS, as the reaction of the teachers, employees a nd, mainly, the students in front of the installation and the works of SCSI.
Keywords: Memória; História oral; Golpe militar; UFRGS; Memory; Oral history; Military coup; ACCNPQ::Ciências Humanas::Educação